Manusia Sempurna Menurut Al-Jili - Dirhamzah Dirhamzah (Al-Hikmah Journal for Religious Studies, 2021)
ABSTRACT This article discusses the concept of "Insan Kamil" according to Al-Jili. The concept of his thought is written in his book entitled "al-Insan al-Kamil fi Ma'rifat-I 'l-awÃ£khir wa' l-AwÃ£'il". A perfect human being according to Al-Jili is a human being the mirror of God or a human being a copy of God. In al-JÃ®lÃ®'s view the most perfect tajalli container of god and none other is Nur Muhammad, according to him Nur Muhammad has existed since before this universe existed. Nur Muhammad moved from one generation to the next in various forms of prophets, starting from the Prophet Adam As to the closing Prophet, then moved to the guardians and ending with the closing guardian (khatam auliyÃ¢), namely Isa as who will descend at the end time. Such is the process of tajalli (self -appearance) of Allah in the universe. His most perfect tajalli container is a perfect human being in the form of the Prophet Muhammad saw. Because the Prophet Muhammad is a human being who is considered to have reached a degree of perfection in his life. Keywords: Al-Jili, Insan Kamil, Nur Muhammad ABSTRAK Artikel ini membahas tentang konsep â€œInsan Kamilâ€™ menurut pandangan Al-Jili. Konsep pemikirannya tersebut ditulis dalam bukunya yang berjudul â€œal-Insan al-Kamil fi Maâ€™rifat-I â€˜l-awÃ£khir wa â€˜l-AwÃ£â€™ilâ€. Insan kamil menurut Al-Jili adalah manusia cermin tuhan atau manusia copy (nuskah) tuhan. Dalam pandangan al-JÃ®lÃ® wadah tajalli tuhan yang paling sempurna dan tidak ada yang lain adalah Nur Muhammad, menurutnya Nur Muhammad telah ada sejak sebelum alam ini ada. Nur Muhammad berpindah-pindah dari satu generasi ke generasi berikutnya dalam berbagai bentuk para nabi, mulai dari Nabi Adam As hingga pada Nabi penutup, kemudian berpindah kepada para wali dan berakhir pada wali penutup (khatam auliyÃ¢), yaitu Isa as yang akan turun pada akhir zaman. Demikian proses tajalli (penampakan diri) Allah pada alam semesta. Wadah tajalli-Nya yang paling sempurna adalah insan kamil dalam wujud Nabi Muhammad saw. Karena Nabi Muhammad-lah manusia yang dinilai telah mencapai derajat kesempurnaan dalam hidupnya.